2019
DOI: 10.1017/s2040174419000163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postnatal overfeeding on the male and female Wistar rat reproductive parameters

Abstract: Overweight/obesity has become a worldwide epidemic, and factors such as a sedentary lifestyle and inadequate eating habits directly contribute to the development of this condition. Studies indicate that rapid weight gain at critical development stages, such as the lactation period, is associated with the development of obesity, cardiovascular diseases, and diabetes in the long term. In addition to metabolic changes during adulthood, overweight/obesity may influence reproductive function of the population. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
4
5
0
Order By: Relevance
“…Reducing litter size to induce postnatal overfeeding has been widely used to study major short‐ and long‐term outcomes of childhood obesity and related metabolic disease. Consistent with previous studies (Costa et al., 2019 ; Li et al., 2016 ; Yzydorczyk et al., 2019 ), our study demonstrated that postnatal overfed induced persistent increases in body weight, abnormal glucose, and hepatic steatosis in adulthood. The most important finding was that postweaning ω3PUFAs diet prevented the weight gain and reduced the risk of NAFLD development by SL rearing.…”
Section: Discussionsupporting
confidence: 93%
“…Reducing litter size to induce postnatal overfeeding has been widely used to study major short‐ and long‐term outcomes of childhood obesity and related metabolic disease. Consistent with previous studies (Costa et al., 2019 ; Li et al., 2016 ; Yzydorczyk et al., 2019 ), our study demonstrated that postnatal overfed induced persistent increases in body weight, abnormal glucose, and hepatic steatosis in adulthood. The most important finding was that postweaning ω3PUFAs diet prevented the weight gain and reduced the risk of NAFLD development by SL rearing.…”
Section: Discussionsupporting
confidence: 93%
“…These two imprinting factors are responsible mainly for causing weight gain and body adiposity accumulation in this programming model. In the present study, neonatal overnutrition due to litter reduction caused an increase in food consumption, body mass, and fat depots in animals, corroborating several data in the literature in males (Habbout et al, 2013 ; Plagemann et al, 1999 ; Rodrigues et al, 2009 ) and the few studies available in females (Costa et al, 2019 ; Voits et al, 1996 ). Here, we approach parameters of the gut‐brain axis in this experimental model to understand whether a possible dysfunction of this system can explain hyperphagia.…”
Section: Discussionsupporting
confidence: 91%
“…However, they exhibit early balanopreputial separation, an external marker of puberty [ 67 ]. At PND 90, the SL male offspring shows reduced mass of the epididymis, seminal vesicle, and ventral prostate, without changes in the spermatic parameters [ 68 ].…”
Section: The Litter Size Reduction Model: Short- and Long-term Effectsmentioning
confidence: 99%
“…On the other hand, female SL offspring exhibit controversial changes at puberty. It has been described as normal [ 67 ], early [ 30 ], or delayed vaginal opening [ 68 ]. Reinforcing the suggestions of early puberty in SL females, they show an early first estrus compared to control animals [ 30 ].…”
Section: The Litter Size Reduction Model: Short- and Long-term Effectsmentioning
confidence: 99%
See 1 more Smart Citation